Human papillomavirus false positive cytological diagnosis in low grade squamous intraepithelial lesion. - Núñez Troconis, José; Delgado, Mariela; González, Julia; Velásquez, Jesvy; Mindiola, Raimy; Whitby, Denise; Conde, Betty; Munroe, David (Investigación Clínica, 2013)
The purpose of this study was to investigate the number of Human Papillomavirus false positive cytological diagnosis in low grade squamous intraepithelial lesions (LSIL). Three hundred and two women who assisted to an Out-Patient Gynecologic Clinic in Maracaibo, Venezuela, were recruited for this study. Each patient had the Pap smear and a cervical swab for Hybrid Capture 2 (HC2). Three cytotechnologists reviewed the Pap smears and two pathologists rescreened all of them. The cytotechnologists reported 161 (53.3%) Pap smears negatives for intraepithelial lesion (IL) or malignancy, and 141 cases (46.7%) with epithelial abnormalities. They reported 46% of 302 patients with HPV infection in Pap smear slides. The pathologists found that 241 (79.8%) Pap smears were negatives for IL or malignancy and 61 (20.2%), with abnormal Pap smears. They found 14.6% HPV infection in all Pap smears (p < 0.0001; 46% vs 14.6%). The HC2 study showed that 47 samples (15.6%) were positive for HPV. The study found that 114 Pap smears (False Positive: 85%) of 134 reported by the cytotechnologists and 24 (False Positive: 43%) of 56 cytologies reported by the pathologists as LSIL, were negative for HPV infection determined by HC2 (p < 0.00003). The present study suggests that the cytotechnologists overdiagnosed cellular changes associated with HPV infection in the Pap smear, increasing the FP cytological diagnosis of LSIL.